Modulation of k-Ras Signaling by Natural Products - B. Bharate, S.; Singh, B.; A. Vishwakarma, R. (Current Medicinal Chemistry, 2012)
Ras proteins regulate diverse cellular pathways that are important in the growth and spread of malignancies, including cell proliferation, cell cycle regulation, cell survival, angiogenesis and cell migration. These proteins lack the conventional transmembrane or hydrophobic domain typical of membrane associated proteins. Being small and hydrophilic in nature, these proteins undergo four-stage post-translational lipid modifications viz. prenylation, AAX proteolysis, carboxymethylation and palmitoylation for membrane localization which is important for their function. Therefore, enzymes involved in these modifications viz. farnesyl transferase (FTase), geranylgeranyl transferase-I (GGTase-I), geranylgeranyl transferase-II (GGTase-II), Ras converting enzyme-1 (Rce-1) and isoprenyl cysteine methyl transferase (ICMT) are emerging as potential therapeutic targets for the discovery of newer anticancer therapeutics. Several natural products have shown modulation of these post-translational enzymes. In the present review, natural products isolated from terrestrial as well as marine sources showing ability to modulate these k-Ras post-translational targets and their promise as potential anticancer agents have been discussed. A total of 157 natural products with 141 corresponding references have been covered.
Keywords: cancer